Relationship Between Employee Engagement and Innovative Behavior: Empirical Study of PT Bank BRI Syariah Tbk in DKI Jakarta, West Java, and Banten - Syahid Izzatuddin; Retno Kusumastuti (Jurnal Administrasi Bisnis, 2021)
The innovative behavior of employee is one of the important triggers in the production of company innovation. Employee engagement is an important factor in encouraging employees to behave innovatively. This study focuses on the relationship between employee engagement and innovative behavior of Bank BRI Syariah employees in the provinces of DKI Jakarta, West Java and Banten. The purpose of this study was to examine the relationship between employee engagement and innovative behavior. This study used a quantitative research approach with data collection techniques through online questionnaire. The sample in this study were 98 permanent employees of Bank BRI Syariah from various areas of responsibility within the provinces of DKI Jakarta, West Java, and Banten. This study used several data analysis techniques, namely the reliability and validity of the questionnaire, descriptive analysis, and the coefficient of correlation test between variables. The results showed a positive and significant relationship between employee engagement and innovative behavior. This study recommends that companies pay more attention to the level of their employee engagement as it has a positive relationship with innovative behavior of the employees, which in turn can increase the company’s innovation potential.